Kontribusi Pengajar Pendidikan Agama Kristen dalam Menumbuhkan Kepercayaan Diri Murid Distabilitas - Lena Anjarsari Sembiring; Auw Tammy Yulianto; Simon Simon (Sekolah Tinggi Theologia Nazarene Indonesia, 2023)
The background of this paper was based on the fact that the contribution of teachers in helping to increase the confidence of students with disabilities had not been significant. The real contribution as a teacher was very necessary, considering that the students who were categorized as disabled in 2020-2021 had reached 144,621 students. The size of students with disabilities was a concern for every one of us, especially teachers, to help educationally and mentally. In describing this paper, the researchers used qualitative methods with a literature study approach. The formulation of questions to be answered in this article, what was the description of the problems of students with disabilities? What was the concrete contribution of PAK teachers in fostering the confidence of these students? The results of the discussion in this article suggested that the problems experienced by students with disabilities were that they received a negative stigma and were vulnerable to mental health.The teachers’ real contribution to help the growth of the students’ self-confidence was carried out through a friendship-based teaching approach, skill-based education and independence-based education. The students' confidence would grow if this was realized and the educators followed Jesus' attitude in humanizing disabled people.